Kemampuan Berbicara Anak Di Tk Pertiwi Desa Rajabasa Lama Kecamataan Labuhan Ratu Kabupaten Lampung Timur - Mega Mulyani; Ulwan Syafrudin; Rizky Drupadi (FKIP UNILA, 2020)
This research is motivated by the lack of children's speaking ability in answering questions given by the teacher and the inability of the child to simply retell the contents of the stories they have heard. The purpose of this study was to improve the speaking skills of group A children in TK Pertiwi Desa Rajabasa Lama. The subjects of this study were 15 children. The data collection techniques used were observation (observation sheets), interviews (interview grids for teachers), and documentation (notes during the activity, pictures or photos, and RKH). The data analysis technique was done using quantitative descriptive. The children's speaking ability reached 48.14% and a decrease in the score obtained reached 6.67%. The teacher provides motivation and rewards in the form of